Substitution potential of plastic fine aggregate in concrete for sustainable production - Ullah, K. (Elsevier Ltd, 2022)
This study evaluates the mechanical and durability characteristics of eco-friendly concrete incorporating electronic plastic waste (EPW) as partial replacement of fine aggregate. This strategy not only reduces the adverse impacts of EPW on the natural environment but also prevents the depletion of natural resources due to excessive quarrying. For this purpose, four M20 grade concrete mixes were prepared, substituting natural fine aggregates with plastic fine aggregates (PFA) using 0, 10, 15, and 20 replacement levels. The mechanical performance of EPW concrete was evaluated based on the compressive and splitting tensile strength tests while the durability properties were assessed through fire resistance, ultrasonic pulse velocity (UPV), alternate wetting and drying, sorptivity coefficient, and abrasion resistance tests. The results revealed that the compressive strength was reduced by 2.6, 9, and 13.6, and tensile strength was dropped by 4.95, 8.20, and 20.46 with the 10, 15, and 20 of PFA incorporation, respectively. Also, a substantial reduction in the compressive strength was observed during the fire resistance test at elevated temperatures. However, the EPW concrete offered satisfactory to superior outcomes in the workability, sorptivity coefficient, UPV, alternative wetting and drying, and resistance to abrasion tests, signifying the potential of EPW concrete for applications where durability is of prime concern. Â© 2021 Institution of Structural Engineers